Involvement of Multiple Variants of Soluble CD146 in Systemic Sclerosis: Identification of a Novel Profibrotic Factor. Issue 6 (11th April 2022) - Nollet, Marie; Bachelier, Richard; Joshkon, Ahmad; Traboulsi, Waël; Mahieux, Amandine; Moyon, Anais; Muller, Alexandre; Somasundaram, Indumathi; Simoncini, Stéphanie; Peiretti, Franck; Leroyer, Aurélie S.; Guillet, Benjamin; et al.
Abstract : Objective: Systemic sclerosis (SSc) is an autoimmune disorder characterized by excessive fibrosis, immune dysfunction, and vascular damage, in which the expression of many growth factors is deregulated. CD146 was recently described as a major actor in SSc. Since CD146 also exists as a circulating soluble form (sCD146) that acts as a growth factor in numerous angiogenic‐ and inflammation‐related pathologies, we sought to identify the mechanisms underlying the generation of sCD146 and to characterize the regulation and functions of the different variants identified in SSc. Methods: We performed in vitro experiments, including RNA‐Seq and antibody arrays, and in vivo experiments using animal models of bleomycin‐induced SSc and hind limb ischemia. Results: Multiple forms of sCD146, generated by both shedding and alternative splicing of the primary transcript, were discovered. The shed form of sCD146 was generated from the cleavage of both long and short membrane isoforms of CD146 through ADAM‐10 and TACE metalloproteinases, respectively. In addition, 2 novel sCD146 splice variants, I5‐13‐sCD146 and I10‐sCD146, were identified. Of interest, I5‐13‐sCD146 was significantly increased in the sera of SSc patients ( P < 0.001; n = 117), in particular in patients with pulmonary fibrosis ( P < 0.01; n = 112), whereas I10‐sCD146 was decreased ( P < 0.05; n = 117). Further experiments revealed that shed sCD146 and I10‐sCD146 displayed proangiogenic activity through the focal adhesion kinase and protein kinase Cε signaling pathways, respectively, whereas I5‐13‐sCD146 displayed profibrotic effects through the Wnt‐1/β‐catenin/WISP‐1 pathway. Conclusion: Variants of sCD146, and in particular the novel I5‐13‐sCD146 splice variant, could constitute novel biomarkers and/or molecular targets for the diagnosis and treatment of SSc and other angiogenesis‐ or fibrosis‐related disorders.